Pathways of child education: from the 1988 constitution to the BNCC - Mello, Ana Paula Barbieri de; Sudbrack, Edite Maria (Universidade Estadual de Campinas, 2019)
In this article, which is part of a master's dissertation, we will present and discuss the main opinions and principles of the legal documents from the 1988 Federal Constitution to the BNCC for Early Childhood Education, in order to understand the contribution of each document to the Policies of Early Childhood Education. It was based on the principles of historical-critical methodology and was delineated theoretically, bibliographical and documentary, with a qualitative approach. We chose the procedure of content analysis for the description, the understanding and the interpretation of the materials found. The results reveal the contradictions between the legislation and the educational practice, as well as the historical constituent aspects of the subject. From the context, it can be concluded that the Public Educational Policies for Early Childhood Education urgently need measures by which politicians and managers invest resources in the educational field, such as: support to teachers and managers with quality training (initial and continued), planning of the infrastructure of work and the materials adapting them to the age group, professional valorization, with the presence of professionals of the education in the elaboration of the laws and public policies, among other actions. This means letting go of the promises, the tireless reforms and the discontinuity of public policies. And we understand that BNCC's analysis is indispensable when we study public education policies, as it is the most recent document of curricular policy.